Designing markets for CO₂ emissions and other pollutants - Johannes Heister; Peter Michelis (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1991)
The objective of this paper is to show how to initiate a market for carbon dioxide and other greenhouse gases by introducing a feasible system of tradeable emission permits, which can be applied as an efficient instrument of environmental policy in single countries and in the whole European Community after the EC internal market is in force. Part one of the paper summarizes the relevant framework conditions of the CO2 problem and briefly reviews possible instruments for CO2 control. Based on this, part two develops an alternative to traditional permit systems. It describes the notion of tradeable emission coupons and applies this concept to CO2 emissions. It deals with the intertemporal allocation of CO2 emissions, opts for the initial distribution of CO2 coupons by auction, stipulates the carbon content of fuel as the assessment base, selects importers and producers as the appropriate addressees of the coupon system for CO2 and solves the (system's initial) problem with end-of-pipe technologies. Finally, it shows how to extend the coupon system to other greenhouse gases. Part three of the paper studies the performance of the system in the framework of the EC's future internal market. And finally, part four deals with a possible application of the emission coupon system to pollutants other than greenhouse gases.
Keywords: 330; Emissionsrechte; Luftverunreinigung; Kohlendioxid; Klimaveränderung; Theorie; Deutschland; EU-Staaten